Bone Morphogenetic Protein 3 Controls Insulin Gene Expression and Is Down-regulated in INS-1 Cells Inducibly Expressing a Hepatocyte Nuclear Factor 1A–Maturity-onset Diabetes of the Young Mutation - Bonner, Caroline (American Society for Biochemistry and Molecular Biology, 2011)
Inactivating mutations in the transcription factor hepatocyte nuclear factor (HNF) 1A cause HNF1A–maturity-onset diabetes of the young (HNF1A-MODY), the most common monogenic form of diabetes. To examine HNF1A-MODY-induced defects in gene expression, we performed a microarray analysis of the transcriptome of rat INS-1 cells inducibly expressing the common hot spot HNF1A frameshift mutation, Pro291fsinsC-HNF1A. Real-time quantitative PCR (qPCR), Western blotting, immunohistochemistry, reporter assays, and chromatin immunoprecipitation (ChIP) were used to validate alterations in gene expression and to explore biological activities of target genes. Twenty-four hours after induction of the mutant HNF1A protein, we identified a prominent down-regulation of the bone morphogenetic protein 3 gene (Bmp-3) mRNA expression. Reporter assays, qPCR, and Western blot analysis validated these results. In contrast, inducible expression of wild-type HNF1A led to a time-dependent increase in Bmp-3 mRNA and protein levels. Moreover, reduced protein levels of BMP-3 and insulin were detected in islets of transgenic HNF1A-MODY mice. Interestingly, treatment of naïve INS-1 cells or murine organotypic islet cultures with recombinant human BMP-3 potently increased their insulin levels and restored the decrease in SMAD2 phosphorylation and insulin gene expression induced by the HNF1A frameshift mutation. Our study suggests a critical link between HNF1A-MODY-induced alterations in Bmp-3 expression and insulin gene levels in INS-1 cells and indicates that the reduced expression of growth factors involved in tissue differentiation may play an important role in the pathophysiology of HNF1A-MODY.